2004
DOI: 10.1029/2003gl018970
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ocean carbon cycle models with data‐based metrics

Abstract: [1] New radiocarbon and chlorofluorocarbon-11 data from the World Ocean Circulation Experiment are used to assess a suite of 19 ocean carbon cycle models. We use the distributions and inventories of these tracers as quantitative metrics of model skill and find that only about a quarter of the suite is consistent with the new databased metrics. This should serve as a warning bell to the larger community that not all is well with current generation of ocean carbon cycle models. At the same time, this highlights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
183
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 188 publications
(204 citation statements)
references
References 14 publications
20
183
1
Order By: Relevance
“…After all, complex models may do rather poorly in tests against observations. For example, a number of ocean carbon cycle models fail to simulate well observed ocean 14 C distributions and, therefore, present day ocean circulation and mixing (Matsumoto et al, 2004). Our calibrations to complex model results have been limited to the choice of a CO 2 fertilization factor for the land biosphere and to the dependence of methane consumption on methane concentration in the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…After all, complex models may do rather poorly in tests against observations. For example, a number of ocean carbon cycle models fail to simulate well observed ocean 14 C distributions and, therefore, present day ocean circulation and mixing (Matsumoto et al, 2004). Our calibrations to complex model results have been limited to the choice of a CO 2 fertilization factor for the land biosphere and to the dependence of methane consumption on methane concentration in the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…For the next IPCC assessment, much could be learned if Earth system models would include one simple passive tracer, like CFC11, in their ocean component (e.g., run optionally for 50 years as one additional passive tracer in the online ocean component). With this one anthropogenic tracer, it would be straightforward to assess ocean model skill in ventilating subsurface waters (e.g., England 1995;Smethie et al 2001;Dutay et al 2002;Matsumoto et al 2004Matsumoto et al , 2010 which is crucial for ocean biogeochemistry. Such simulations were performed routinely a decade ago for evaluating ocean circulation component of ocean carbon models during OCMIP.…”
Section: Discussionmentioning
confidence: 99%
“…Modeled CFC11 in surface waters is generally quite similar, being essentially set by atmospheric CFC11 and SST patterns. But, modeled CFC11 in subsurface waters and inventories can differ greatly providing information on ocean dynamics (e.g., Matsumoto et al 2004). Global inventories of CFC11 are about 4.3 9 10 8 , 6.3 9 10 8 , and 6.4 9 10 8 mol for CNRMCM5, IPSLCM4 and IPSLCM5, respectively.…”
Section: Cfc11 and Cfc12 Distributionmentioning
confidence: 99%
“…A lesson from OCMIP-2 was that the uptake of anthropogenic transient tracers is quite variable in different ocean carbon cycle models because their physics, defined in the broadest sense (e.g., resolution, forcings, numerics, sea ice, seasonality, GM), was so diverse Dutay et al, 2002;Matsumoto et al, 2004). OCMIP-2 showed that biogeochemical tracers are very effective in evaluating the ventilation rate of the ocean interior, because the tracers have built-in clocks.…”
Section: Calibration and Control Run Of Mesmomentioning
confidence: 99%